SERUM MYOGLOBIN DYNAMICS IN PATIENTS WITH ESSENTIAL HYPERTENSION AND EPISODES OF SILENT MYOCARDIAL ISCHEMIA - S. Y. Bebeshko; T. N. Ardamatskaya; T. V. Rozhdestvenskaya; A. N. Burlaka; I. A. Ivanova (Российский кардиологический журнал)
The aim of this research was to study the clinical meaning of dynamic of blood serum mioglobine level in hypertensives with episodes of painless ishemia of hypertrophied miocardium 128 patients (23 women among them) with hypertension desease II stage (according to WHO classification, 1993) aged between 35 and 58 years (average age 25,3±1,2 year) were treated by through-oesophagus stimulation of auricles, ECG daily monitoring was conducted, 24-hours profile of serum Mg was studied. Nature of structural and functional miocardium changes and their correlation with frequency of painless ishemia of myocardium was analized. Results:duration of painless depression of ST segment is proportionally and significantly correlated with MMLV (r=0,88 p<0,01). Group of GD II stage with high level serum Mg after TOSA-test significantly differed both in the quantity of episodes of painless depression of ST segment (12,5±2,69 against 5,66±0,86 , p<0,002) and for their duration (4,1±1,02 against 2,45±0,41 min, correspondingly, p<0,001). Clinical moment of Mg level increase in GD II stage patients was defined.